2020
DOI: 10.1016/j.heliyon.2020.e04822
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of common bean varieties (Phaseolus vulgaris L.) to different row-spacing in Jimma, South Western Ethiopia

Abstract: This study evaluated the effect of row spacing on growth, yield and yield components of common bean varieties at Jimma. The objectives of the study were (i) to evaluate the best performed common bean variety (ii) to determine the optimum row spacing for different common bean varieties under the test environment. The experiment was laid out in randomized complete block design (RCBD) in factorial arrangement with three replications. A combination of three common bean Varieties (Nasir, Goberesha and Local Asendab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 8 publications
3
13
1
Order By: Relevance
“…It is possible that the variation in the number of pods per plant is due to the genetic factor and not the plant density. This result is contrary to Merga (2020) who reported a significant difference in the interaction between bean varieties and row spacing. Present findings also agree with the results of Kiriba et al (2020) who reported no significant effect of plant density on number of seeds per pod and 100 seed weight of bush bean varieties.…”
Section: Analysis Of Variance (Anova)contrasting
confidence: 99%
See 1 more Smart Citation
“…It is possible that the variation in the number of pods per plant is due to the genetic factor and not the plant density. This result is contrary to Merga (2020) who reported a significant difference in the interaction between bean varieties and row spacing. Present findings also agree with the results of Kiriba et al (2020) who reported no significant effect of plant density on number of seeds per pod and 100 seed weight of bush bean varieties.…”
Section: Analysis Of Variance (Anova)contrasting
confidence: 99%
“…Present findings also agree with the results of Kiriba et al (2020) who reported no significant effect of plant density on number of seeds per pod and 100 seed weight of bush bean varieties. Moreover, other studies that evaluated the bean varieties for different row spacings also reported non-significant effects of the interaction between bean varieties and row spacing (Asemanrafat and Honar, 2017;Merga, 2020) which are in agreement with this study. Conversely, these results are contrary with the results of Musana et al…”
Section: Analysis Of Variance (Anova)supporting
confidence: 91%
“…[ 11 ], by Refs. [ 5 , 34 ] on common bean. Several studies on the common bean yield due to varietal performance reported that the difference of grain yield is attributes to many factors including the genetic performance, environmental adaptation, and the resistance to biotic and abiotic stresses [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Congo) is the ninth African country in terms of tonnage of common bean produced (172 833.03 tons) after Tanzania (844 024.59 tons), Uganda (651 385.08 tons) and Kenya (499 624.56 tons) who are the first three bean producers in Africa [ 3 ]. Common bean is widely cultivated across all cropping systems (monoculture and/or intercropping), commonly associated with cereals and/or perennial crops and contributes to significantly improve soil fertility [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high competition for growth factors, crops planted at narrower interrow spacing had high growth and vegetative mass due to the production of auxin hormones and higher light interception at the upper layer of the canopy that enabled the higher total biomass and grain yields. As the authors of reference [39] found, the grain yield increased as interrow spacings became narrower and narrower due to increased vegetative growth of crop which resulted in a high assimilation rate of crops for further conversion of biological yield into economic yield. In agreement with these ideas, the authors of reference [40] stated that, as interrow spacings increased the grain yield plant −1 increased and grain yield ha −1 decreased due to low plant populations per a given area and higher nutrient availability to the crops to enhance excessive vegetative growth.…”
Section: Grain Yield (Kg/tonmentioning
confidence: 99%